2017
DOI: 10.4103/jcvjs.jcvjs_73_17
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgical treatment for Kimmerle anomaly

Abstract: Introduction:Kimmerle anomaly is the bony ridge between the lateral mass of atlas and its posterior arch or transverse process. This bony tunnel may include the V3 segment of the vertebral artery, vertebral vein, posterior branch of the C1 spinal nerve, and the sympathetic nerves, which results in the clinical symptoms of this disease. Reports on the surgical treatment of Kimmerle anomaly are rare. There are no reports on minimally invasive surgical treatment of this pathology.Materials and Methods:Six patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, recent studies about PP seem to focus on its association with headache and its implications during the placement of lateral mass screws in the atlas 17,20,21 . Until now, only six studies have described the surgical treatment of PP (Table 1) 3,5,[8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies about PP seem to focus on its association with headache and its implications during the placement of lateral mass screws in the atlas 17,20,21 . Until now, only six studies have described the surgical treatment of PP (Table 1) 3,5,[8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…PP occurs at rates of 1.1%-37% according to different studies 2,3 . This bony canal usually includes the V3 segment of the vertebral artery (VA) and may also include the accompanying vein, sympathetic nerves, posterior C1 spinal nerve, and posterior branch of the C1 spinal nerve 5 . Therefore, compression or irritation of these structures by PP with spinal movement may lead to the clinical signs 5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that AF contains all these other neurovascular structures causes pressure on VA within the foramen. As a matter of fact, AF decompression is applied in these cases considering that VBI Clinic in Barre Lieou syndrome is formed by this mechanism (19,20). However, although clinical improvement was achieved in most of the cases with foramen decompression, 13.33% of young patients without cervical arthrosis also reported not to respond completely to treatment (19).…”
Section: Discussionmentioning
confidence: 99%
“…Cadaver studies are an important method in elucidating the ethiopathogenesis of diseases and determining the treatment. It is thought that AF causes Barre Lieou syndrome, which also includes vertebrobasilar insufficiency (VBI) findings, by compressing the structures within AF, therefore foramen decompression is performed in its treatment (19,20). However, only one study was found in the literature in English (18).…”
Section: Introductionmentioning
confidence: 99%